2009
DOI: 10.3390/ijms10093743
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of the NO3 Radical Addition to Double Bonds of Limonene

Abstract: The addition reactions of NO3 to limonene have been investigated using ab initio methods. Six different possibilities for NO3 addition to the double bonds, which correspond to the two C–C double bonds (endocyclic or exocyclic) have been considered. The negative activation energies for the addition of NO3 to limonene are calculated and the energies of NO3-limonene radical adducts are found to be 14.55 to 20.17 kcal mol-1 more stable than the separated NO3 and limonene at the CCSD(T)/6–31G(d) + CF level. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…Recently, Xu et al . performed theoretical calculation on the addition of NO 3 to CC double bond in limonene . They explained the branching ratio of the final product by calculating the energy and activation energy of the radical intermediate produced by the addition of NO 3 to two CC double bonds in limonene.…”
Section: Total Energies For the Species Involved In The Reactions Of supporting
confidence: 69%
“…Recently, Xu et al . performed theoretical calculation on the addition of NO 3 to CC double bond in limonene . They explained the branching ratio of the final product by calculating the energy and activation energy of the radical intermediate produced by the addition of NO 3 to two CC double bonds in limonene.…”
Section: Total Energies For the Species Involved In The Reactions Of supporting
confidence: 69%
“…Theoretical investigations have revealed that NO3 addition on the endocyclic C=C double bond is more favorable than the exocyclic one due to a lower energy barrier (Jiang et al, 2009). Typically, in the limonene + NO3 reaction, the endocyclic double bond of limonene tends to be attacked by NO3 and leads to products including hydroxysubstituted ON or diketone products.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction mechanism involves the initial addition of NO3 across a double bond to form a nitrooxyalkyl radical, which, in air, forms a nitrooxyalkyl peroxy radical. Product studies suggest that attack of NO3 at the exocyclic double bond of limonene is insignificant (Spittler et al 2006), which is supported by theoretical calculations (Jiang et al, 2009).…”
Section: Comments On Preferred Valuesmentioning
confidence: 57%